Penerapan Restrukturisasi Perjanjian Kredit Perbankan Menurut Peraturan Otoritas Jasa Keuangan Nomor 11/POJK.03/2020 Dalam Kaitannya Dengan Konsep Wanprestasi Dan Force Majeur Menurut Hukum Perdata Di Indonesia - Trouwelijk, Salsabila; Putra, Mohamad Fajri Mekka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Bank credit restructuring is a change in the provisions of the credit agreement between the bank and its customers as a form of creditor forgiveness for defaults committed by the debtor. The Covid-19 pandemic that has hit Indonesia since the beginning of 2020 has caused many debtors to default on bank credit. The pandemic situation that caused a domino effect on the banking sector was then managed through the existence of the Financial Services Authority Regulation Number 11/POJK.03/2020. This study analyzes the form of legal protection for debtors in banking activities related to defaults arising from the pandemic based on the Civil Code and government policies through POJK for debtors during a pandemic. The research method used is normative juridical by using an approach to legislation and general legal concepts. The results of the study show that the Covid-19 pandemic is a form of force majeure which makes it possible to change the agreement to carry out obligations at another time if agreed by the parties. Government policy through POJK No. 11/POJK.03/2020 for debtors to save credit during the Covid-19 pandemic by using a restructuring mechanism.